THE ROLE OF PRODUCT INNOVATION IN IMPROVEMENT OF SUPPLY CHAIN PERFORMANCE AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF TECHNICIANS WHO WORK IN ENGINEERING OFFICES AND MEDICAL LABORATORIES DEPLOYED IN SOME IRAQI GOVERNORATES - Sajjad Raad Khalaf Hussien; Prof Dr. Atheer Abdul Ameer Hassoni (Scholar Express Journals, 2023)
The study sought to search for the role of product innovation in improving of supply chain performance with its dimensions (quality, flexibility, cost, delivery) in engineering offices and medical laboratories deployed in some Iraqi governorates (Baghdad, Babyl, Najaf, Karbala , Mosul, Erbil). The problem of the study was to ask The main (what is the role of product innovation in improving supply chain performance ), the study sample included technicians working in engineering offices and medical laboratories, and the questionnaire was used to collect data, as the number of responses was (192) an answer It was obtained from the technicians working in those engineering offices and medical laboratories deployed in some Iraqi governorates. The random sampling method was adopted. The research used the descriptive analytical approach in the study, and then the data was analyzed by adopting some statistical methods such as (the arithmetic mean, standard deviation, linear correlation coefficient, simple and multiple regression coefficient) and the scale was tested using (Alpha Cronbach, factor analysis), and the results were reached using Statistical programs such as (SPSS.V.27) and (Amos.V.26), where the results of the study confirmed that there are Role to product innovation in supply chain performance.
Keywords: product innovation; supply chain performance